Designing An Accounting Information System Based On Microsoft access at PT ADC SENTRAL JAYA - Androni Susanto; Kelly Kelly (ConCEPt - Conference on Community Engagement Project, 2023)
PT ADC Sentral Jaya is a marine supply chain company that sells batteries and solar panel equipment also offers battery services located in Batam, Kepulauan Riau Islands. All financial transactions are still recorded manually with Microsoft Excel, making not effective and efficient for bookkeeping, and impacted not producing financial reports that comply with standards. Based on this, the community service activity aims to design an accounting information system that is user friendly for users who do not have an accounting background. The system will be based on Microsoft Access Database. The method used is the method of observation, interviews, and documentation. This Microsoft Access system consists of sales form, purchase, account list estimate, list of goods, customer list, supplier list, sales, and purchase payments. In addition to the form for inputting data, there are financial statements, consists of profit and loss, financial position and equity as well as reports on overall sales, battery sales, and purchases. Reports and implementation of this system are running well and effectively, making this system can be used as an example or adopted by similar companies.